Analysis of Escherichia coli and Salmonella sp. Contamination in Snacks and Food Handlers of Elementary School Children in West Bekasi - Afrinia Ekasari; Arindah Nur Sartika; Maulin Inggraini; Reza Anindita (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Food safety is a preventive measure against the risk of disease caused by microorganisms, chemicals, and physical materials that can contaminate food. Salmonella sp. and E. coli is a common food poisoning agent found in school snacks. Elementary school students are a vulnerable group to microbial contamination due to their frequent snacking habits. Therefore, this study aims to analyze E. coli and Salmonella sp. contamination in school snacks in the West Bekasi school area, Bekasi City. The research design of this study was a laboratory-based experiment. Data collection method: Data was collected from three different locations: SDN Bintara 1, SDN Jakasampurna 1 and SDN Kotabaru 3. Snack food testing was carried out using TPC testing, to determine the presence of E. coli contamination using EMBA media and Salmonella sp. using SSA media. The result of TPC is above 71,4% of school children’s snacks are classified as unsafe only 4 types of food are classified as safe, namely onigiri, papeda, cilor, and meatballs on skewers. There are 2 foods that grow in EMBA media, namely udang rambutan and cibay, it is possible that both foods are contaminated with E. coli.